Inovação em serviços: estudo multicasos em concessionárias automotivas - Haluch , Edson Luiz (2016)
The current research is a multiple cases analysis, which contains quantitative reflections of the innovation process of services spread between three automotive dealerships of different sizes and cities. Automotive dealerships have been innovating on its selling format, through more complex technologies and innovative services, which require updates in the managing process. This study shows the relevance of the customer/supplier relation, through the engagement of both parts on the development of new services, therefore, creating a trustworthy relationship between them. The research method used here is an exploratory and qualitative one, based on a semi-structured questionnaire, with the goal of analyzing the actions of service innovation, which include the clients and the automotive dealerships’ necessities and interests. The conclusion of this study for a great size automotive dealership is that there is a concern on retaining clients and embroiling them over the establishment and management of innovations. Also, this great size dealership has an innovative culture, with a high level with a high level costumer involvement of customers on the development of new actions. To the medium size dealership, it was highlighted that there is an innovative culture, although there's no compatible internal structure for the clients’ needs, who demonstrate having interest on participating on the development of new services, but there's no straight mean of communication for the clients and the dealership. Moreover, there's the need to enhance the management of the suggestions proposed by the employees and the clients, thereby, creating the processes of client loyalty and the sharing of experiences. On the small size dealership, there's no formal and structured process referring to the creation and development of new services. Furthermore it has no organizational or technological capacity to arrange the learning from the clients' suggestions and apply this knowledge to develop projects on innovative services. For further research, it's suggested to look for new brands and different sized automotive dealerships, on which is possible to explore, in a more effective way, the connection between the development of new services and the involvement of the clients